Qualifications, Discrimination, or Assimilation? An Extended Framework for Analysing Immigrant Wage Gaps - Helena Skyt Nielsen; Michael Rosholm; Nina Smith; Leif Husted (Institute for the Study of Labor (IZA), 2001)
In this paper, we analyze immigrant wage gaps and propose an extension of the traditional wage decomposition technique, which is a synthesis from two strains of literature on ethnic/immigrant wage differences, namely the ?assimilation literature? and the ?discrimination literature?. We estimate separate wage equations for natives and a number of immigrant groups using panel data sample selection models. Based on the estimations, we find that the immigrant wage gap is caused by a lack of qualifications and incomplete assimilation, and that a large fraction of that gap would disappear if only immigrants could find employment and thus accumulate work experience.
Keywords: J71; J15; J16; J31; 330; Wage assimilation; immigrants; wage gap; panel data sample selection model; Migranten; Ethnische Gruppe; Lohnstruktur; Lohndifferenzierung; Qualifikation; Soziale Integration; Arbeitsmarktdiskriminierung; Schätzung; Dänemark